2021
DOI: 10.3390/ijerph18052210
|View full text |Cite
|
Sign up to set email alerts
|

Dizziness Handicap Inventory in Clinical Evaluation of Dizzy Patients

Abstract: (1) Objectives: The evaluation of dizzy patients is difficult due to nonspecific symptoms that require a multi-specialist approach. The Dizziness Handicap Inventory (DHI) is widely used in the assessment of dizziness-related disability, but its clinical efficacy needs further expansion. The aim of this study was to identify the subscales of DHI that may correlate with some vestibular or nonvestibular dysfunctions. (2) Material and methods: This observational study included 343 dizzy patients with one of the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…By objective genetic testing, our results revealed that the expression of all examined circadian clock genes did not significantly associate with DHI total score, as well as the physical, emotional and functional subscales scores in patients with MD. Our data imply that the dizziness handicap degree of MD is independent of circadian rhythm, but may be mainly influenced by the compensated and uncompensated status of vestibular dysfunction 48 …”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…By objective genetic testing, our results revealed that the expression of all examined circadian clock genes did not significantly associate with DHI total score, as well as the physical, emotional and functional subscales scores in patients with MD. Our data imply that the dizziness handicap degree of MD is independent of circadian rhythm, but may be mainly influenced by the compensated and uncompensated status of vestibular dysfunction 48 …”
Section: Discussionmentioning
confidence: 65%
“…Our data imply that the dizziness handicap degree of MD is independent of circadian rhythm, but may be mainly influenced by the compensated and uncompensated status of vestibular dysfunction. 48 Within the postulated mechanisms behind the formation of endolymphatic hydrops in MD, oxidative stress of the inner ear was thought of as one of the causal factors. [49][50][51] Overproduction of reactive oxygen species is well known as the major contributor to the damage of hair cells in acquired hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…The DHI is likely multidimensional in nature but that the dimensions are substantially different from the functional, emotional, and physical disability subscales. Items of the DHI do not evaluate the otological or neurovegetative symptoms which mostly accompany to vestibular symptoms, and do not assess the effects of dizziness on self-care activities [4,24].We only calculate the total scores, we should calculate subscale scores to assess the Physical manifestations, Catastrophic impact, and Emotional Impact of dizziness on the dizzy patient. PFO closure has demonstrated its effect in CS patients with PFO [25][26][27][28], and three randomized studies [29][30][31] and ve meta-analyses have addressed the issue of percutaneous closure as therapy for migraine [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…The score ranges from 0 (disabled) to 100 (very independent). The self-perceived level of handicap associated with the symptom of dizziness is measured by the 25-item Dizziness Handicap Inventory (DHI) [26]. Both ADL and GHI are self-report questionnaires.…”
Section: Data Collectionmentioning
confidence: 99%